2018
DOI: 10.1158/2326-6066.cir-17-0211
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity GD2-Specific CAR T Cells Induce Fatal Encephalitis in a Preclinical Neuroblastoma Model

Abstract: The GD2 ganglioside, which is abundant on the surface of neuroblastoma cells, is targeted by an FDA-approved therapeutic monoclonal antibody and is an attractive tumor-associated antigen for cellular immunotherapy. Chimeric antigen receptor (CAR)–modified T cells can have potent antitumor activity in B-cell malignancies, and trials to harness this cytolytic activity toward GD2 in neuroblastoma are under way. In an effort to enhance the antitumor activity of CAR T cells that target GD2, we generated variant CAR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(208 citation statements)
references
References 32 publications
11
189
0
1
Order By: Relevance
“…Cytokine release syndrome (CRS) and CAR T cell related encephalopathy syndrome (CRES) are well described unique toxicities associated with CAR T cells and some other immunotherapies [28][29][30][31][32][33] ; however, the pathophysiological mechanisms of both CRS and CRES remain poorly understood. Results from animal studies reported in May 2018 implicate recipient monocyte derived and/or macrophage derived IL1, IL6, and nitric oxide (and not CAR T cell derived cytokines) as the key determinants of the severity of CRS and CRES 34,35 .…”
mentioning
confidence: 99%
“…Cytokine release syndrome (CRS) and CAR T cell related encephalopathy syndrome (CRES) are well described unique toxicities associated with CAR T cells and some other immunotherapies [28][29][30][31][32][33] ; however, the pathophysiological mechanisms of both CRS and CRES remain poorly understood. Results from animal studies reported in May 2018 implicate recipient monocyte derived and/or macrophage derived IL1, IL6, and nitric oxide (and not CAR T cell derived cytokines) as the key determinants of the severity of CRS and CRES 34,35 .…”
mentioning
confidence: 99%
“…72,73 CD19-CAR-T cells with the CD28 co-stimulatory domain reportedly induce earlier onset CRS relative to their 4-1BB-containing counterparts 69 and have been associated with fatal cerebral edema perhaps because of earlier and higher peak expansion of CAR-T cells, which were derived from cell products containing a greater preponderance of CD8 + T cells and obtained from younger patients with more vigorous cellular immunity. 66,76 However, when a high-affinity variant of the 14g2a scFv was created, intracerebral infiltrates of these GD2-CAR-T cells were detected and associated with fatal neurotoxicity in the mice. 72 Other relatively minor modifications to the CAR such as altering the length of the linker between the light and heavy chains of the CAR's scFv moiety can also have a profound impact on the in vivo function of CAR-T cells.…”
Section: Car-t Cell Designmentioning
confidence: 99%
“…For instance, a GD2 directed CAR-T is in development for neuroblastoma and brain tumors. [42][43][44][45] CAR-T recognizing multiple antigens (eg CD19 and CD22, CD19 and CD123) or infusion of both CD19 and CD22 directed CAR-T at the same time are under investigation to limit recurrence of resistant (ie antigen negative) tumor cells. [46][47][48] Each iteration of CAR-T and each tumor type presents specific challenges that research must overcome including anti-inflammatory tumor milieu, antigen expression on healthy cells and side effects of CAR-T administration and activation.…”
Section: Similar Observations On Intrinsic T-cell Factors Affecting Cmentioning
confidence: 99%
“…Neurologic toxicity has also previously been seen in other immunotherapeutic modulators such as Blinatumomab and is also seen after CD22 directed CAR-T as well as preclinical models of GD2-directed CART. 43,81,82 The neurological deficits seen in the days and weeks after CAR-T infusion are varied, however encephalopathy is the most common severe side effect. Similar to CRS, CRES can be mild to severe.…”
Section: Cell -Rel Ated En Cephalopathy Syndrome/immune Effec Tor Cmentioning
confidence: 99%